Influence of Thermal Processing on Resoloy Wire Microstructure and Properties. Issue 4 (25th January 2021) - Xue, Ju; Griebel, Adam J.; Zhang, Yaping; Romany, Cristina; Chen, Bowen; Schaffer, Jeremy; Weihs, Timothy P.
Abstract : Magnesium fine wires are critical components for the fabrication of various absorbable implants. Herein, Resoloy fine wires with diameters of 200 and 500 μm are prepared with a multipass, cold‐drawing technique before undergoing two brief thermal anneals at 350 or 450 °C. The as‐drawn, cold‐worked (CW) wires show small but elongated α‐Mg grains, with their long axes and basal planes parallel to the drawing direction. Fine, continuous, and uniformly distributed Mg24 Dy5 particles are observed within the wire. Although the brief anneals at 350 and 450 °C do not alter the texture of the Mg grains or the area fraction, aspect ratio, or distribution of the secondary phase, they do enable recovery and partial recrystallization at 350 °C and complete recrystallization at 450 °C, thereby providing a wide range of mechanical properties. The 200 μm wires display slightly higher strengths and slightly lower elongations. Modified simulated body fluid (m‐SBF) immersion results indicate that the Resoloy wires exhibit relatively uniform corrosion with rates as low as 1.72 ± 0.09, 1.44 ± 0.21, and 1.97 ± 0.10 mm y −1 for the cold‐worked, 350 °C, and 450 °C wires with 500 μm diameter, respectively. Abstract : Resoloy wires with diameters of 200 and 500 μm are prepared with a multipass, cold‐drawing technique before undergoing thermal anneals at 350 or 450 °C. With proper heat treatment, Resoloy wires show relatively uniform corrosion with satisfactory corrosion resistance along with a wide range of mechanical properties, which makes them a strong candidate for fabrication of biodegradable implants.